ON-THE-JOB TRAINING PROGRAM EFFECTIVENESS AND PERFORMANCE OF BSIT STUDENTS OF CSU GONZAGA - Suetos, E R (Proceedings of the International Conference on Education, 2023)
This study aimed to assess the On-the-Job Training (OJT) program effectiveness and performance of Bachelor of Science in Information Technology (BSIT) students at Cagayan State University (CSU) Gonzaga campus. Specifically, it sought to determine the profile of the respondents, their overall perception of the effectiveness of the OJT program, their level of OJT performance, and the potential relationships between these variables. The study employed descriptive-correlational techniques and collected data through questionnaire and Performance Evaluation Reports (PERs). The analysis included aspects such as pre-deployment orientation, work assignment, monitoring from school, training and support from agencies, cooperation among trainees, and evaluation and post-deployment activities. The research revealed that trainees perceived the OJT program to be very effective overall, with specific aspects such as pre-deployment orientation, work assignment, monitoring, and cooperation being particularly effective. The respondents also demonstrated excellent performance in various OJT aspects, including quality of work, job knowledge, and human relations. Notably, academic performance (GPA) was found to be positively correlated with OJT performance, suggesting that higher academic achievement correlates with better OJT performance. Moreover, the effectiveness of training and support from agencies positively influenced the quantity of work and human relations performance. This study's implications for the College of Information and Computing Sciences (CICS) and higher education are significant. It emphasizes OJT's role in enhancing practical skills and bridging academics with real-world skills. A strong link exists between academic performance and OJT success, underlining the need for rigorous educational standards. Insights on effective OJT, like agency support and collaboration, can enhance programs for better career readiness. Overall, the study underscores experiential learning's value and industry-academic collaboration in higher education.